Effects of Self-Management Interventions Based on Shared Decision-Making in Patients with Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis. - Choi, Ja Yun; Yeon Lim, Su; Yun, So Young (Korean Journal of Adult Nursing, 2026)
Purpose: This systematic review and meta-analysis examined the effects of shared decision- making (SDM)-based self-management interventions on health outcomes in patients with chronic obstructive pulmonary disease (COPD). Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, three databases were searched in July 2022, supplemented by gray literature and citation searching. Randomized controlled trials that integrated SDM components into COPD self-management programs were included. Two reviewers independently performed study selection, data extraction, and risk-of-bias assessment. Random-effects models were used to pool odds ratios (ORs) for dichotomous outcomes and standardized mean differences (SMDs) for continuous outcomes, with 95% confidence intervals (CIs). Outcomes included hospital readmission, health-related quality of life (HRQoL), functionality, physical symptoms, psychological symptoms (depression and anxiety), and self-efficacy. Results: Seven studies (n=1,028) met the inclusion criteria. SDM-based interventions showed no statistically significant difference in hospital readmission (OR=1.59, 95% CI, 0.79 to 3.19; I²=49.1%) and no significant improvement in HRQoL (SMD=0.19, 95% CI, -0.14 to 0.51; I²=98.3%). Depression showed no significant effect (SMD= -0.01, 95% CI, -0.39 to 0.38; I²=98.1%). Self-efficacy improved slightly (SMD=0.12, 95% CI, 0.01 to 0.23; I²=89.4%), with substantial heterogeneity. Evidence for other secondary outcomes was inconsistent. Conclusion: SDM-based self-management interventions did not demonstrate clear benefits for hospital readmission or HRQoL in patients with COPD. Given the heterogeneity across studies, these findings should be interpreted cautiously. Future trials should use standardized SDM frameworks, assess implementation fidelity, and apply consistent outcome measures to clarify the role of SDM in COPD management.